Absenteeism: a retrospective cross–sectional study among employees of the Keratsini Municipality for the year 2022 - Sarros, Georgios; Menti Ariadni,; Katrachouras Ioannis,; Stergiakouli Vasiliki,; Makrynos George,; Rapisarda Venarando,; Georgios Dounias, (International Journal of Occupational Safety and Health, 2026)
Introduction: Absenteeism is a multifactorial phenomenon. The study aimed to analyze specific indicators (Absenteeism rate, Frequency of sickness absence, Cumulative incidence, Duration of absence, Length of sickness absence, Bradford Score) among municipal employees and to compare them across certain variables (gender, position, age, seniority).Methods: In this retrospective cross-sectional study, the sample was the employees of the Municipality of Keratsini for year 2022. Data were collected through the individual employees’ sick leave file, processed with Microsoft Excel and statistically analyzed with Stata (chi-square tests). A comparison of the results between two previous studies with the same sample followed.Results: Females (n=179/45.8%) received statistically sick leave more frequently (females with at least one sick leave: n=148/82.7%, males with at least one sick leave: n=128/60.4%) (p